Polymorphisms KIF12 GENE|BfaI and its Association on Carcass Characteristics and Lamb Meat Quality - Raudah Putri Ekawati; Ratna Sholatia Harahap; Kasita Listyarini; Cece Sumantri; Asep Gunawan (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
One of gene which involves on mediation an antioxidant cascade in beta cells as an intracellular target of excess fat intake is Kinesin Family 12 (KIF12). This study aims to identify the diversity of SNP g. 9617965 C>T KIF12 and association with carcass characteristic and meat quality. The total sample used were 102 ram DNA samples consisted of 10 barbados cross sheep (BCS), 52 javanese thin tail (JTT), 15 jonggol sheep (JS), 15 garut sheep (GS), and 10 compass agrinak sheep (CAS). Identification of the diversity of KIF12|BfaI was conducted using the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method. The results showed that the amplification product was 696 bp. The diversity of the KIF12 gene was found three genotypes namely CC, CT, and TT. The allele frequency in all types of sheep was in Hardy-Weinberg equilibrium. A SNP of the KIF12 was associated (P<0.05) with characteristic of carcass, including length of carcass. The association of KIF12 with meat quality was significant (P<0.05) too associated with pH and water holding capasity (WHC). It could be concluded that KIF12 gene is a potential candidate gene for carcass characteristic and meat quality traits in sheep